Pengaruh Terapi Activity Daily Living terhadap Pemulihan Pasien Halusinasi - Suhermi Suhermi; Rahmawati Ramli; Hasriani Caing (FORIKES, 2021)
Mental health is a condition where an individual can develop physically, mentally, spiritually, and socially so that the individual is aware of his own abilities, can deal with pressure, can work productively, and is able to contribute to his community. Recovery is also the process by which a person is able to live, work, study and participate fully in his community. This study aims to determine the effect of daily living activity therapy on the recovery of hallucinatory patients in DADI Province South Sulawesi Hospital. The research design used was a pre-experimental design with one-group pre-post test design without control. The sample was determined by using purposive sampling technique, so that the samples were determined according to the inclusion criteria, namely patients with hallucinatory nursing diagnoses who were in the recovery process as many as 20 respondents. The results showed that there was an effect of daily activity therapy on the recovery process of hallucinatory patients (p = 0.00). So, there is an effect of daily activity therapy on the recovery process of hallucinations in Cempaka Room of RSKD DADI Province of South Sulawesi. It is therefore expected that nurses increase the daily administration of therapeutic activities in hallucinatory patients because the therapy is very influential on the patient's recovery process. Keywords: activity daily living; hallucinatory; recovery ABSTRAK Kesehatan jiwa merupakan kondisi dimana seorang individu dapat berkembang secara fisik, mental, spiritual, dan sosial sehingga individu tersebut menyadari kemampuan sendiri, dapat mengatasi tekanan, dapat bekerja secara produktif, dan mampu memberikan kontribusi untuk komunitasnya. Pemulihan merupakan proses dimana seseorang mampu untuk hidup, bekerja, belajar dan berpartisipasi secara penuh dalam komunitasnya. Penelitian ini bertujuan untuk mengetahui pengaruh terapi activity daily living terhadap pemulihan pasien halusinasi di RSKD DADI Provinsi Sulsel. Desain penelitian yang digunakan adalah pra experimental dengan rancangan one-group pre-post test design without control. Penentuan sampel dilakukan dengan teknik purposive sampling, sehingga menentukan sampel sesuai kriteria inklusi yaitu pasien dengan diagnosa keperawatan halusinasi yang dalam proses pemulihan sebanyak 20 responden. Hasil penelitian menunjukkan bahwa ada pengaruh terapi aktivitas harian terhadap proses pemulihan pasien halusinasi (p=0,00), sehingga ada pengaruh terapi activity daily living terhadap proses pemulihan pasien halusinasi di ruang Cempaka RSKD DADI Prov Sulsel. Oleh karena itu diharapkan pada perawat agar meningkatkan pemberian terapi aktivitas harian pada pasien halusinasi karena terapi tersebut sangat berpengaruh terhadap proses pemulihan pasien. Kata kunci: kegiatan harian; halusinasi; pemulihan